2015
DOI: 10.1016/j.ydbio.2015.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila KASH-domain protein Klarsicht regulates microtubule stability and integrin receptor localization during collective cell migration

Abstract: During collective migration of the Drosophila embryonic salivary gland, cells rearrange to form a tube of a distinct shape and size. Here, we report a novel role for the Drosophila KASH (Klarsicht-Anc-Syne Homology) domain protein Klarsicht (Klar) in the regulation of microtubule (MT) stability and integrin receptor localization during salivary gland migration. In wild-type salivary glands, MTs became progressively stabilized as gland migration progressed. In embryos specifically lacking the KASH domain contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…They also showed that nesprin-1α regulates MT nucleation [100]. In Drosophila , KASH domain protein Klarsicht regulates MT stability and integrin localization during collective cell migration [101]. These results indicate a physical role for the nucleus as anchoring point for cytoplasmic cytoskeletal elements.…”
Section: Effects Of Ne On the Cytosolic Cytoskeletonmentioning
confidence: 99%
“…They also showed that nesprin-1α regulates MT nucleation [100]. In Drosophila , KASH domain protein Klarsicht regulates MT stability and integrin localization during collective cell migration [101]. These results indicate a physical role for the nucleus as anchoring point for cytoplasmic cytoskeletal elements.…”
Section: Effects Of Ne On the Cytosolic Cytoskeletonmentioning
confidence: 99%
“…g-TURC is released from the centriole in a spastin-dependent manner and is then anchored to the apical membrane through the transmembrane protein Piopio. As embryogenesis proceeds and salivary gland and tracheal cells migrate collectively to form tubes, MTs become progressively stabilized and extend along the apicobasal axis (Brodu et al 2010;Myat et al 2015).…”
Section: Microtubule Organization and Motor Proteins In Animal Tissuementioning
confidence: 99%
“…Importantly, both the AKT and the profibrotic TGFβ pathways that drive cardiac hypertrophy and interstitial fibrosis are mechanoresponsive, largely through pathways sensitive to inputs from cellular adhesions and/or the state of the actomyosin cytoskeleton (Iijima et al , 2002; Balasubramanian and Kuppuswamy, 2003; Gomez et al , 2010; Young et al , 2014; Hinz, 2015; O’Connor et al , 2015; Varney et al , 2016). Models of LINC complex ablation provide an opportunity to test whether communication of mechanical signals from the cytoskeleton to the nuclear interior (Lammerding et al , 2004; Lee et al , 2007; Hale et al , 2008; Stewart-Hutchinson et al , 2008; Luxton et al , 2010; Folker et al , 2011; Khatau et al , 2012; Long et al , 2013; Myat et al , 2015; Stewart et al , 2015) contributes to myocardium function, although to date this avenue of investigation has been largely unexplored.…”
Section: Introductionmentioning
confidence: 99%